An unusual case of polyostotic fibrous dysplasia-A case report - Kiran Suresh Jagtap; Nikita Rajendrakumar Patel; Poonam Hiray; Anjali Wadhwa (Wolters Kluwer Medknow Publications, 2020)
Fibrous dysplasia (FD) is a fibro-osseous lesion where normal bone and marrow is replaced with fibrous tissue, resulting in formation of bone that is weak and prone to expansion. It is classified according to the number of affected bones, and its association to endocrine alterations, that is, monostotic (80-85%), polyostotic forms (20-30%), and Albright's disease. Involvement of two or more bones is termed as polyostotic FD, a relatively uncommon condition. Here we report a rare case of polyostotic FD involving facial bones, orbital bones, sphenoid bone, and spine in a 21-year-old male patient.